Factors that determine parents’ awareness on the use of cash waqf for educational assistance in Malaysia - Abdul Razak, Dzuljastri; Mohamed Sofian, Nurul Hashimah; Mazlan, Nurul Huda (2017)
Waqf is a charitable institution that has long been practiced from the time. Prophet Muhammad(pbuh). In Malaysia, waqf has been used for several purposes like building of mosque, cemeteries and poverty alleviation. The use of cash waqf is gaining prominence due to its flexibility. However, the availability of cash waqf as a means for educational assistance is still newbut has been increasing important. This is because of the scarcity of government scholarships due for financial constraints. Another option is study financing from banks and PTPTN which incurred financial charges.